Growth differentiation factor-11 downregulates steroidogenic acute regulatory protein expression through ALK5-mediated SMAD3 signaling pathway in human granulosa-lutein cells - Qiongqiong Jia; Boqun Liu; Xuan Dang; Yanjie Guo; Xiaoyu Han; Tinglin Song; Jung-Chien Cheng; Lanlan Fang (BMC, 2022)
Abstract Background Growth differentiation factor-11 (GDF-11) belongs to the transforming growth factor-β (TGF-β) superfamily. To date, the expression of GDF-11 in the ovary and its role in regulating ovarian function are completely unknown. Ovarian granulosa cell-mediated steroidogenesis plays a pivotal role in maintaining normal female reproductive function. GDF-11 and GDF-8 share high sequence similarity and exhibit many similar features and functions. Steroidogenic acute regulatory protein (StAR) regulates the rate-limiting step in steroidogenesis and its expression can be downregulated by GDF-8. Polycystic ovary syndrome (PCOS) is the most common cause of female infertility. The expression levels of GDF-8 are upregulated in the human follicular fluid and granulosa-lutein (hGL) cells of PCOS patients. However, whether similar results can be observed for the GDF-11 needs to be determined. Methods The effect of GDF-11 on StAR expression and the underlying molecular mechanisms were explored by a series of in vitro experiments in a primary culture of hGL cells obtained from patients undergoing in vitro fertilization (IVF) treatment. Human follicular fluid samples were obtained from 36 non-PCOS patients and 36 PCOS patients. GDF-11 levels in follicular fluid were measured by ELISA. Results GDF-11 downregulates StAR expression, whereas the expression levels of the P450 side-chain cleavage enzyme (P450scc) and 3β-hydroxysteroid dehydrogenase (3β-HSD) are not affected by GDF-11 in hGL cells. Using pharmacological inhibitors and a siRNA-mediated approach, we reveal that ALK5 but not ALK4 mediates the suppressive effect of GDF-11 on StAR expression. Although GDF-11 activates both SMAD2 and SMAD3 signaling pathways, only SMAD3 is involved in the GDF-11-induced downregulation of StAR expression. In addition, we show that SMAD1/5/8, ERK1/2, and PI3K/AKT signaling pathways are not activated by GDF-11 in hGL cells. RT-qPCR and ELISA detect GDF-11 mRNA expression in hGL cells and GDF-11 protein expression in human follicular fluid, respectively. Interestingly, unlike GDF-8, the expression levels of GDF-11 are not varied in hGL cells and follicular fluid between non-PCOS and PCOS patients. Conclusions This study increases the understanding of the biological function of GDF-11 and provides important insights into the regulation of ovarian steroidogenesis.